Role of Gene Polymorphisms of Matrix Metalloproteinases-2, -3 and -13 in the Development of Coronary Artery Atherosclerosis in Patients with Primary Polyosteoarthrosis - O. O. Portyannikova; E. N. Romanova; A. V. Govorin; S. M. Tsvinger (Архивъ внутренней медицины)
The aim of the research. To assess the influence of polymorphisms of the matrix metalloproteinase genes — 2 (rs2285053), — 3 (rs3025058), and — 13 (rs2252070) on the development of coronary atherosclerosis in patients with primary osteoarthritis.Materials and methods. The polymorphisms of the Thе pоlymоrphisms оf thе matrix metalloproteinase genes — 2 (rs2285053), — 3 (rs3025058), and — 13 (rs2252070) and their connection with development of atherosclerosis in patients with osteoarthritis were determined.Results. In the process of studying the polymorphism (rs2252070 T/C) of the MMP — 13 gene, it was revealed that the carriage of the homozygous T allele of the MMP-13 gene polymorphism is 1,8 times higher in the group of patients without verified coronary atherosclerosis in comparison with a group of patients with verified coronary atherosclerosis. This fact shows that this genotypic variant is protective in relation to the development of atherosclerotic lesions of the coronary vessels. The heterozygous variant of the T/C genotype was more common in the group of patients with verified coronay atherosclerosis — 59%. The calculation of the odds ratio shows that the possibility of developing coronary atherosclerosis in patients with this genotype is 2,7 times higher than in patients with a homozygous grnotypic variant.Conclusion. It is shown that the heterozygous variant of rs2252070 T/C matrix metalloproteinase 13 increases the chance of developing coronary atherosclerosis in patients with osteoarthritis.